ANALYSIS OF THE EFFECT OF CORRESPONDENCE MANAGEMENT WITH MANUAL DISPOSITION ON EMPLOYEE PERFORMANCE IN ADMINISTRATIVE SERVICES AT THE FACULTY OF SOCIAL AND POLITICAL SCIENCES, UNIVERSITAS NEGERI SEMARANG - Purwanto; rahmawati, Farida; Bambang Hermanto (Universitas Negeri Semarang, 2025)
This study is intended to analyze the effect of correspondence management with manual disposition on the performance of administrative services at the Faculty of Social and Political Sciences, Universitas Negeri Semarang. The focus of the study is on correspondence management and instructions on manual disposition sheets implemented at Faculty of Social and Political Sciences, Universitas Negeri Semarang. The urgency of this study is to be able to identify and overcome problems related to correspondence management with instructions on manual disposition sheets in administrative services at Faculty of Social and Political Sciences, Universitas Negeri Semarang. This study uses a quantitative approach by testing the formulated hypothesis. The data used in this study are primary data obtained from a survey by distributing questionnaires to all administrative employees at Faculty of Social and Political Sciences, Universitas Negeri Semarang. Determination of the sample based on Hair's suggestion, namely, 5-10 times the number of research indicators (Hair, 2009). In this study there are 11 indicators, so in this study the sample used was 55 people. The results of the study indicate that correspondence management with manual disposition has an impact on the performance of administrative services at the Faculty of Social and Political Sciences, Universitas Negeri Semarang, namely the better the correspondence management with manual disposition applied, the performance of administrative services at the Faculty of Social and Political Sciences, Universitas Negeri Semarang will also increase. Conversely, if the worse the correspondence management with manual disposition applied, the performance of administrative services at the Faculty of Social and Political Sciences, Universitas Negeri Semarang will also decrease